Is cooperation better than competition? Evidence from patient mobility before and after the COVID-19 pandemic in Tuscany, Italy - Giovanni Guarducci; Davide Golinelli; Luca Spadea; Giuliana Fabbri; Nicola Nante; Nicola Nante (Frontiers in Public Health, 2025)
IntroductionAccording to Italian Law, citizens have the right to choose the preferred place of care; in this context, the competition between various hospitals across the national territory is inevitable. The study aims to analyze the associations between patient mobility between Tuscany (Italy) and other Italian regions and the weight of Diagnosis Related Groups (DRGs) provided for these hospitalizations, as a proxy of complexity of care provided.MethodsA retrospective study was conducted using 2019 and 2022 Hospital Discharge Cards data of Tuscany provided by the Italian Ministry of Health. The surgical DRGs of each Major Diagnostic Categories (MDCs) were considered according to high specialty (HS) and non-high specialty (N-HS). For each MDCs, patient attractions and escapes to bordering and non-bordering regions with Tuscany were associated with HS and N-HS surgical discharge DRGs by using Odds Ratios (OR). The analysis was performed thought STATA software, and the significance level was set at 95%.ResultsIn studied period, for Digestive Diseases (in 2019 OR: 1.37; 95%CI: 1.08–1.74; in 2022 OR: 1.66; 95%CI: 1.29–2.12), patients from non-border regions were more likely to be attracted to the Tuscany hospitals for HS DRGs, while for Musculoskeletal Diseases (in 2019 OR: 0.51; 95%CI: 0.47–0.56; in 2022 OR: 0.53; 95%CI: 0.48–0.59), those from non-border regions were less likely to be attracted for HS DRGs (p < 0.05). For the same years, for Nervous Diseases (in 2019 OR: 3.08; 95%CI: 2.18–4.37; in 2022 OR: 2.27; 95%CI: 1.60–3.22) and for Hepatobiliary and Pancreas Diseases (in 2019 OR: 4.56; 95%CI: 2.71–7.68; in 2022 OR: 4.19; 95%CI: 2.35–7.47). Tuscan patients were more likely to escape to non-border regions for HS DRGs while for Musculoskeletal Diseases (in 2019 OR: 0.76; 95%CI: 0.68–0.84; in 2022 OR: 0.83; 95%CI: 0.72–0.89) they were less likely to be admitted to non-border regions for HS DRGs (p < 0.05).ConclusionThe findings highlight the need to implement interregional agreements to optimize patient mobility, avoid duplication of services, reduce costs and improve access to care.